2018
DOI: 10.1002/er.3976
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of an integrated solar-based power generation plant using nanofluids

Abstract: Summary In this present paper, a thermo‐economic analysis is carried to study the performance and feasibility of using nanofluids as heating fluids in an integrated solar power generation plant (ISPGP). The integrated power generation plant consists of the solar field that is represented by parabolic trough solar collectors (PTSCs), a thermal energy storage system, and a power block. The effect of dispersing copper (Cu) and silver (Ag) nanoparticles into Therminol VP‐1 and Syltherm 800 fluids is investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…The change in viscosity is intimately related to heat transfer enhancement of nanofluids in particular when buoyancy forces are present, as in the present study, as will be elaborated in due course. Thus viscosity variation as studied by the Reynolds model may provide a good insight into the improved efficiencies reported in solar energy systems doped with nanofluids at higher temperatures as noted by Cingarapu et al [17], Alashkar and Gadalla [20].…”
Section: Pumping Characteristicsmentioning
confidence: 83%
See 3 more Smart Citations
“…The change in viscosity is intimately related to heat transfer enhancement of nanofluids in particular when buoyancy forces are present, as in the present study, as will be elaborated in due course. Thus viscosity variation as studied by the Reynolds model may provide a good insight into the improved efficiencies reported in solar energy systems doped with nanofluids at higher temperatures as noted by Cingarapu et al [17], Alashkar and Gadalla [20].…”
Section: Pumping Characteristicsmentioning
confidence: 83%
“…eqns. (19), (20) and 21 (48) Here denotes fourth-order Runge-Kutta phase and is the fifth-order Runge-Kutta phase. An estimate of the error is achieved by subtracting the two values obtained.…”
Section: Validation With Maple17mentioning
confidence: 99%
See 2 more Smart Citations
“…They found that toluene with CuO nanoparticles was the optimal combination. Alashkar and Gadalla [13] tested nanofluids including Syltherm 800 and Therminol VP-1 with Cu and Ag in a parabolic trough solar collector to run the Rankine Cycle. Their findings show that the annual energy production rose by 11.7%.…”
Section: Introductionmentioning
confidence: 99%